Influence of Ice Nuclei Parameterization Schemes on the Hail Process. (20th February 2018) - Liu, Xiaoli; Fu, Ye; Cao, Zhibin; Jin, Shuanglong
Abstract : Ice nuclei are very important factors as they significantly affect the development and evolvement of convective clouds such as hail clouds. In this study, numerical simulations of hail processes in the Zhejiang Province were conducted using a mesoscale numerical model (WRF v3.4). The effects of six ice nuclei parameterization schemes on the macroscopic and microscopic structures of hail clouds were compared. The effect of the ice nuclei concentration on ground hailfall is stronger than that on ground rainfall. There were significant spatiotemporal, intensity, and distribution differences in hailfall. Changes in the ice nuclei concentration caused different changes in hydrometeors and directly affected the ice crystals, and, hence, the spatiotemporal distribution of other hydrometeors and the thermodynamic structure of clouds. An increased ice nuclei concentration raises the initial concentration of ice crystals with higher mixing ratio. In the developing and early maturation stages of hail cloud, a larger number of ice crystals competed for water vapor with increasing ice nuclei concentration. This effect prevents ice crystals from maturing into snow particles and inhibits the formation and growth of hail embryos. During later maturation stages, updraft in the cloud intensified and more supercooled water was transported above the 0°C level, benefitting the production and growth of hail particles. An increased ice nuclei concentration therefore favors the formation of hail.